Xinjiang of China its past and present - Li, Sheng 1949- (China Intercontinental Press, 2013)
This is a book focuse on the historical and current affairs concerning stability and development in Xinjiang. It has been written with the purpose of respecting history, clarifying the truth, and basing on the reality.